Perlindungan Hukum terhadap Pariwisata Cagar Alam dan Budaya di Bali - Nofri Y Naihati; Ida Bagus Anggapurana Pidada (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Tourism is one of the most important economic sectors in the world, contributing significantly to state revenue and improving people's welfare. The tourism industry has grown rapidly in recent decades, with the number of international tourists continuing to increase. The general objective of this study is to develop a deeper knowledge and understanding of the impact of uncontrolled tourism on the sacredness of Bali's nature and culture, as well as strategies for developing sustainable tourism in Bali. The type of research used by the author in examining the problems in this study is normative juridical research. The conclusion of this study is a legal review of the protection of natural and cultural heritage in Bali Province is regulated in several laws and regulations such as Law No. 5 of 1990 concerning the Conservation of Biological Natural Resources and Ecosystems. In addition, cultural protection in Bali has also been regulated in several laws and regulations such as Law No. 11 of 2010 concerning Cultural Heritage. This legal review will also discuss the implementation of laws and regulations related to the protection of natural and cultural heritage in Bali. The Bali provincial government's policy on the protection of natural and cultural heritage, namely the policy on the protection of natural heritage is regulated in the Governor's Regulation or Pergub No. These include Law No. 97 of 2018 concerning the Limitation of Single-Use Plastic Waste, Governor Regulation No. 45 of 2019 concerning Bali Clean Energy, Governor Regulation No. 48 of 2019 concerning the Use of Battery-Based Electric Motorized Vehicles, and Governor Regulation No. 8 of 2019 concerning Organic Farming Systems. Cultural heritage protection policies are regulated by Law No. 10 of 2010 concerning Tourism, Regional Regulation No. 2 of 2023 concerning the Bali Provincial Spatial Plan (RTRWP), the Designation of Cultural Heritage Areas in Bali, such as Ulun Danu Batur Temple and Lake Batur, the Subak Cultural Landscape and Temples in the Pakerisan Watershed, and others.